Invest Wisely, Save Smartly: Unleashing Your Financial Potential - Ainur Rizki; Yochi Elanda; Asep Saeful Falah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study delves into the intricate dynamics of financial potential among Bank Sumut's clientele, focusing on the interrelationships between investment decisions, saving habits, financial literacy, and financial potential. Using a quantitative research design and employing Smart PLS analysis, data was collected from a sample of 100 bank customers through random sampling. The findings reveal significant direct effects of investment decisions, saving habits, and financial literacy on financial potential, underscoring their crucial roles in shaping individuals' financial capabilities. Additionally, the study uncovers significant indirect effects, highlighting the mediating role of financial literacy in the relationships between investment decisions, saving habits, and financial potential. These results emphasize the importance of promoting financial literacy alongside encouraging prudent saving habits and informed investment decisions to enhance customers' overall financial well-being. The insights derived from this research offer valuable implications for Bank Sumut and similar financial institutions in designing effective strategies to empower their clientele towards achieving long-term financial stability and success.